Preparation of low-cost adsorbent material from chicken bones and its removal of As(III) and Pb(II) toxic ions from wastewater - Upreti, Rita; Jha, Vinay Kumar (Scientific World, 2025)
The low-cost adsorbent was prepared from chicken bone by pyrolysis at 700 ℃ for 1 hour in three different atmospheric conditions, such as Chicken Bone Adsorbent Materials in open air (CBAM-O), in nitrogen (CBAM-N) gas and in nitrogen gas and water steam (CBAM-NS). The specific surface areas of chicken bone adsorbent materials were determined by methylene blue adsorption method and found for CBAM-O, CBAM-N and CBAM-NS as 127, 130 and 206 m2/g, respectively. Present study deals with the adsorption of As(III) and Pb(II) from aqueous solution on CBAM-NS adsorbent. The influence of various parameters like pH, contact time and concentration of adsorbate were studied. Studies showed that the maximum efficiency was achieved at pH 5 for As(III) and Pb(II). Kinetics and isotherm model studies demonstrated that the experimental data fitted with pseudo-second order and Langmuir isotherm model with the rate constants 0.0449 and 0.0354 g/(mg.min) and the maximum adsorption capacities 100 and 163.934 mg/g for As(III) and Pb(II) respectively. The values of ∆G obtained from Langmuir equation was -21, -23 kJ/mole for As(III) and Pb(II) respectively. The negative values of free energy (∆G) in adsorption process revealed the spontaneous nature and feasibility of the adsorption process for the adsorption of As(III) and Pb(II) onto CBAM-NS. The values of ∆G further confirmed that the adsorption process was favoured by physio-chemical-adsorption for As(III) and Pb(II) respectively. The values of the separation parameter KL were found to be 0 ≤ KL ≤ 1 which revealed good adsorption of As(III) and Pb(II) onto CBAM-NS.